2010
DOI: 10.1097/mcd.0b013e3283359386
|View full text |Cite
|
Sign up to set email alerts
|

Pericentric inversion, inv(14)(p11.2q22.3), in a 9-month old with features of Goldenhar syndrome

Abstract: Goldenhar syndrome, also called hemifacial microsomia or oculo-auriculo-verterbal dysplasia (OAVS) (MIM 164210), is a birth defect involving the first and second branchial arch derivatives with an incidence of 1/5000. The variable phenotype includes mostly unilateral deformity of the external ear and small ipsilateral half of the face with epibulbar dermoid and vertebral anomalies. A genome-wide search in one family suggested linkage to a region of 10.7 cM on chromosome 14q32; however, no candidate genes have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…Interestingly, the proband suffered a range of clinical signs resembling HFM, including facial asymmetry, mandibular hypoplasia, and ear defects in addition to developmental delay, lacrimal duct stenosis, and renal anomalies. Northup et al [32] reported a large pericentric inversion inv(14)(p11.2q22.3) in a proband with HFM signs, inherited from his phenotypically normal mother. Ballesta-Martinez et al [33] recently published a clinical report of a 14q22 duplication in a Spanish family with variable phenotypes resembling HFM.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the proband suffered a range of clinical signs resembling HFM, including facial asymmetry, mandibular hypoplasia, and ear defects in addition to developmental delay, lacrimal duct stenosis, and renal anomalies. Northup et al [32] reported a large pericentric inversion inv(14)(p11.2q22.3) in a proband with HFM signs, inherited from his phenotypically normal mother. Ballesta-Martinez et al [33] recently published a clinical report of a 14q22 duplication in a Spanish family with variable phenotypes resembling HFM.…”
Section: Resultsmentioning
confidence: 99%
“…Familial instances compatible with autosomal dominant inheritance have been observed [Tasse et al, ; Vendramini‐Pittoli and Kokitsu‐Nakata, ] in about 2–10% of cases. Linkage analysis in families with autosomal dominant inheritance and array‐CGH analysis have detected candidate loci for OAVS offering new insights into the understanding of pathogenesis of this entity [Kelberman et al, ; Callier et al, ; Ou et al, ; Rooryck et al, ; Huang et al, ; Northup et al, ; Rooryck et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the proband suffered a range of clinical signs resembling HFM including facial asymmetry, mandibular hypoplasia, and ear defects in addition to developmental delay, lacrimal duct stenosis and renal anomalies. Northup et al [32] reported a large pericentric inversion inv(14)(p11.2q22.3) in a proband with HFM signs, inherited from his phenotypically normal mother. Ballesta-Martinez et al [33] recently published a short clinical report of a 14q22 duplication in a Spanish family with variable phenotypes resembling HFM.…”
Section: Resultsmentioning
confidence: 99%